Indeks Pengukuran Penentuan Had Tempoh Mualaf di Malaysia - Azman, A.R; Wan Mohd. Fazrul Azdi, W. R; Nuradli Ridzwan Shah, M.D; Rose Irnawaty, Ibrahim; Norlina Ismail; Irwan Mohd Subri; Mahazan Abdul Mutalib @ Talib (USIM Press, 2024)
Journal of Fatwa Management and Research Volume 6 No.1 Page (39-63)